Dual‐Mode Vasodilator M119 Delivery to Hair Follicle via Dissolving Microneedle for Advanced Alopecia Treatment (Adv. Therap. 8/2022). Issue 8 (18th August 2022) - Kim, Youseong; Ryu, Yeong Chan; Min, Hye Su; Yang, Huisuk; Nam, Jeehye; Lee, Chisong; Um, Daniel Junmin; Kim, Miji; Atzei, Paola; Francisco, Rita de Brito; Naef, Reto; Choi, Kang‐Yell; et al.
Abstract : The dissolving microneedle loading vasodilatorTOP‐M119 (M119) penetrates the scalp and releases the drug to the blood vessels. TheM119 drug induces vasodilation and angiogenesis, and it causes vascularization around hair follicles supplying oxygen and nutrients. This mode of action of M119 drug finally affects alopecia hair follicles' conversion to anagen and hair growth. This is reported by Hyungil Jung and co‐workers in article number 2200052 .